Computer in English language learning / Magarete Thresa - Thresa, Magarete (Universiti Teknologi MARA Cawangan Pahang, 1992)
This article examines and discusses the practical potential of computer-assisted language learning in specific areas of English language teaching namely in the Reading and Vocabulary, Grammar and Writing Components. Some existing ready-to-use and 'authoring' softwares arc also highlighted but one must bear in mind that a computer program is a flexible language-learning aid and so a particular program can be useful for more than one language skill : it is up to the teacher which area of language is given the most emphasis at anyone time.